Farm size and participation in agri-environmental measures: Farm-level evidence from Slovenia - İlkay Unay-Gailhard; Štefan Bojnec (Land Use Policy, 2015)
This paper analyses the determinants of farmer participation in agri-environmental measures (AEMs) using the Slovenian Farm Accountancy Data Network (FADN) during the 2004–2010 period. Previous papers have not shown a straightforward relationship between farm size and decisions to participate in AEM. Considering explicitly the farm size, the controversial subject of the role of farm size is investigated by conducting logit regression analyses. We examine the influence of farm-specific characteristics on participation in AEMs using three different farm sizes: small, medium, and large. The findings strongly suggest that there are differences between the determinant factors of AEM participation based on farms' utilised agricultural area, particularly between small and large farms. This conclusion is supported by those variables that describe farm capital per land intensity, off-farm income and type of farming as significant determinants for large farm models but not for small farm models. Furthermore, variables that describe land productivity negatively influence participation in AEMs for large farms, whereas these variables positively influence the participation of small farms. The results highlight the importance of how these previously confirmed factors influencing AEM participation differ according to the three different farm sizes.
Keywords: 330; Agri-environmental measures; Farm size; Land use; FADN; Logit model; Slovenia